2019
DOI: 10.3390/agronomy10010002
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Streamflow and Nutrient Loadings in a Semi-Arid Mediterranean Watershed with Ephemeral Streams Using the SWAT Model

Abstract: Predicting the availability and quality of freshwater resources is a pressing concern in the Mediterranean area, where a number of agricultural systems depend solely on precipitation. This study aims at predicting streamflow and nonpoint pollutant loads in a temporary river system in the Mediterranean basin (Sulcis area, Sardinia, Italy). Monthly discharge, suspended sediment, nitrate nitrogen, total nitrogen, mineral phosphorus, and dissolved oxygen in-stream monitoring data from gauge stations were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…It has been successfully applied to watershed research in different countries and regions and is one of the most widely used hydrological models for evaluating water resources in different types of basins globally [16][17][18][19][20][21]. For example, Pulighe et al [22] used the SWAT model to predict the runoff and nutrient load of a Mediterranean semiarid small watershed, and the evaluation results from the model were found to be consistent with observed values. Pradhan et al [23] applied the SWAT model and an artificial neural network to basins in tropical, subtropical, arid, and semiarid regions in Asia and showed that the SWAT model and the artificial neural network model performed better when used in low-and high-flow simulations instead of average traffic, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…It has been successfully applied to watershed research in different countries and regions and is one of the most widely used hydrological models for evaluating water resources in different types of basins globally [16][17][18][19][20][21]. For example, Pulighe et al [22] used the SWAT model to predict the runoff and nutrient load of a Mediterranean semiarid small watershed, and the evaluation results from the model were found to be consistent with observed values. Pradhan et al [23] applied the SWAT model and an artificial neural network to basins in tropical, subtropical, arid, and semiarid regions in Asia and showed that the SWAT model and the artificial neural network model performed better when used in low-and high-flow simulations instead of average traffic, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…The SWAT model is a distributed hydrological model, and several studies showed that the SWAT model can be better applied to simulate not only streamflow and runoff but also nutrient loadings, water quality, pollution, etc., all over the world in different climate regions [28][29][30][31][32][33][34][35].…”
Section: Kappa Coefficientmentioning
confidence: 99%
“…The SWAT model was developed to predict the impact of land management practices on water, sediments and agricultural chemical yields in ungauged river basins [14]. The model is widely used in hydrological [8,26] and water-quality analyses at the basin scale [27,28] to assess the impact of land-use changes or climate changes on surface waters [19,29].…”
Section: Quantifying Point and Non-point Source Pollutionmentioning
confidence: 99%